2007
DOI: 10.1111/j.1464-410x.2007.06659.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and significance of circulating epithelial cells in patients with hormone‐refractory prostate cancer

Abstract: The urological oncology section is relatively long this month, and this reflects the many high‐quality manuscripts we receive. When you consider our relatively high rejection rate, you will understand just how many papers on this topic are submitted. The high quality of oncology papers is clear in this month’s section. You will also notice that all but one of them are on prostate cancer, and the reason for this is similar to that mentioned above, as this topic is, as might be expected, the most commonly submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Approximately 10 mL of blood was subjected to IE/FC as previously described (11,13,(16)(17)(18). All IE/FC samples were processed within 36 hours.…”
Section: Ctc Enumeration With Ie/fcmentioning
confidence: 99%
“…Approximately 10 mL of blood was subjected to IE/FC as previously described (11,13,(16)(17)(18). All IE/FC samples were processed within 36 hours.…”
Section: Ctc Enumeration With Ie/fcmentioning
confidence: 99%
“…Previous work by others in breast (6,9) and colorectal (5) cancers and by ourselves and others in castration-resistant prostate cancer (8,10,23) have shown its prognostic importance without quantitation of its predictive strength. Although it is a factor in a prognostic nomogram (13), baseline Gleason score was not predictive of overall survival in our study.…”
Section: Discussionmentioning
confidence: 99%
“…By using reverse transcription-PCR and prostate-specific membrane antigen as mRNA marker for monitoring CTCs in clinically localized PCa patients during radical prostatectomy, a previous report also showed significant correlations of CTCs with advanced tumor stages and increasing Gleason scores (28). Furthermore, the isolation of CTCs by immunomagnetic capture and flow cytometry fluorescenceactivated cell sorting showed that the CTC counts were strongly associated with survival of patients with progressive castrationresistant or hormone-refractory PCa (5,10). The use of a diagnostic antibody targeting the insulin-like growth factor-IR epitope showed that insulin-like growth factor-IR -positive CTCs were most common in advanced hormone-refractory PCa (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, bone marrow aspiration is an invasive procedure, and therefore, many groups have focused on the detection of circulating tumor cells (CTC) in the peripheral blood of PCa patients (5 -13). The clinical utility of CTC counts in PCa is under active investigation with some promising clinical data from single institutions (5,7,8,10). The possibility of detecting tumor cell dissemination years before the onset of metastasis may allow an early curable therapeutic intervention and improve the clinical management of PCa patients.…”
mentioning
confidence: 99%